Veiled Exoneration: The Collision of Freedom of Contract and the Principle of Justice in Digital-Era Consumer Standard Clauses - Maranatha Purba; Maidin Gultom; Ica Karina; Janus Sidabalok (Jurnal Smart Hukum (JSH), 2026)
The proliferation of digital platforms has normalized the use of standard form contracts, often concealing exculpatory clauses that effectively exonerate businesses from liability while binding consumers to non-negotiable terms. This article examines the latent tension between the principle of freedom of contract (partij autonomie) and the principle of justice within boilerplate consumer agreements in the digital ecosystem. Although freedom of contract serves as the doctrinal foundation of private law, its uncritical application in adhesive contracts frequently produces substantively unfair outcomes, particularly when consumers are presented with take-it-or-leave-it terms masked by digital consent mechanisms such as clickwrap and browsewrap agreements. This study employs a normative legal methodology, analyzing statutory regulations, judicial decisions, and comparative legal frameworks to deconstruct how veiled exoneration operates in practice. The findings reveal a structural asymmetry: while standard clauses enhance transactional efficiency, they systematically undermine procedural and substantive justice by shifting risks disproportionately onto consumers. Furthermore, the digital environment exacerbates this disparity through information asymmetry, algorithmic opacity, and the absence of meaningful bargaining power. This article argues that reconciling contractual freedom with justice demands a recalibrated regulatory approach that incorporates good faith obligations, enhanced disclosure duties, and judicial oversight over unconscionable terms. Ultimately, the paper contends that the digital era necessitates a rethinking of contract law doctrine, moving beyond formal consent toward a more equitable framework that safeguards consumer rights without wholly negating contractual autonomy.